7S protein is more effective than total soybean protein isolate in reducing plasma cholesterol. (September 2017) - Liu, Yuwei; Yang, Juan; Lei, Lin; Wang, Lijun; Wang, Xiaobo; Ying Ma, Ka; Yang, Xiaoquan; Chen, Zhen-Yu
Highlights: Soybean seeds have two major storage proteins 11S and 7S. 7S protein is more effective in reducing cholesterol than total soybean protein. 7S protein inhibited cholesterol absorption and enhanced bile acid excretion more than total soybean proteins. 7S protein up-regulated CYP7A1 and HMG-CoA reductase. Screening and cultivation of 7S-enriched soybean cultivars or lines are suggested. Abstract: 7S protein is one of four major storage proteins in soybean. The present study compared the relative cholesterol-lowering activity of the 7S protein with that of total soybean protein isolate (SPI). Forty-eight hamsters were divided into six groups fed non-cholesterol diet or one of five high-cholesterol diets containing 24.2% casein, 12.1–24.2% SPI, 12.1–24.2% 7S protein, respectively. Results showed the 7S protein reduced plasma total cholesterol (TC) by 20–41% while SPI reduced it by 9–16%. 7S protein increased the fecal excretion of neutral sterols by 43–116%, while SPI only had 18–68% increase. 7S protein increased the excretion of total bile acids by 208–367%, while SPI only increased it by 41–86%. 7S protein could not only down regulate gene expression of HMG-CoA reductase but also up regulate gene expression of CYP7A1. It was concluded that dietary 7S protein was more hypocholesterolemic than SPI, mediated by increasing the sterol excretion and decreasing the cholesterol synthesis.